Screening and cloning of pectate lyase genes from Bacillus subtilis isolated in Vietnam - Thu Hang, Do Thi; Bac, Vo Hoai; Truong, Le Van (Academia Journal of Biology, 2013)
Pectate lyase (PL) is an important enzyme in plant pathogenesis, PL is secreted by microorganisms. PL degrades polygalacturonate of plant cell wall product oligogalacturonates. In this report, we described the screening of nine strains of B. subtilis, which isolated from Vietnam with ability to produce pectate lyase. The optimal pH for enzymatic degradation of polygalacturonate was from 8.5 to 10. The genes encoding pectate lyase from 4 different strains were cloned in E. coli and sequenced. Pectate lyase of these 4 strains contains 420 amino acid (aa). The deduced amino acid sequence of these PLs showed 98.8-99.8 % identity to PL from B. subtilis 168. There are 9 aa positions were changed in the amino acid sequencing of 4 trains in comparison between them and B. subtilis 168. The amino acid sequences of PLs of strains from plant were more conserve than those of PLs of strains from soil in comparison with PL from B. subtilis 168.